2014
DOI: 10.1186/s12879-014-0644-7
|View full text |Cite
|
Sign up to set email alerts
|

Enterobiasis and strongyloidiasis and associated co-infections and morbidity markers in infants, preschool- and school-aged children from rural coastal Tanzania: a cross-sectional study

Abstract: BackgroundThere is a paucity of data pertaining to the epidemiology and public health impact of Enterobius vermicularis and Strongyloides stercoralis infections. We aimed to determine the extent of enterobiasis, strongyloidiasis, and other helminth infections and their association with asymptomatic Plasmodium parasitaemia, anaemia, nutritional status, and blood cell counts in infants, preschool-aged (PSAC), and school-aged children (SAC) from rural coastal Tanzania.MethodsA total of 1,033 children were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 69 publications
1
21
1
5
Order By: Relevance
“…however it was less than the prevalence reported in primary school children (38%) in Ragama in Sri Lanka. 11 Furthermore, the prevalence in our study population was very high compared to those reported in other countries including Korea (9.2%-18.5%), 12 China (6.85%), 13 Taiwan (0.62%), 14 rural coastal Tanzania (16.7%-26.3%) 15 and Venezuela (19.1%). 16 In contrast, a comparatively high prevalence was reported in Turkey (43.8%), 17 Thailand (38.7%) 18 and Mongolia 35.8%.…”
Section: Prevalence Of Enterobius Vermicularismentioning
confidence: 71%
“…however it was less than the prevalence reported in primary school children (38%) in Ragama in Sri Lanka. 11 Furthermore, the prevalence in our study population was very high compared to those reported in other countries including Korea (9.2%-18.5%), 12 China (6.85%), 13 Taiwan (0.62%), 14 rural coastal Tanzania (16.7%-26.3%) 15 and Venezuela (19.1%). 16 In contrast, a comparatively high prevalence was reported in Turkey (43.8%), 17 Thailand (38.7%) 18 and Mongolia 35.8%.…”
Section: Prevalence Of Enterobius Vermicularismentioning
confidence: 71%
“…Given this fi nding and the presence of elevated monocyte counts in the strongyloidiasis group, it is unsurprising that lower relative neutrophil counts were detected in the strongyloidiasis group than in the S. stercoralis-negative group. The association between strongyloidiasis and eosinophilia has been well established, although the absence of this correlation has also been reported in the literature (28) (29) .…”
Section: S Stercoralis-s Stercoralispositive (N=167) Negative (N=133)mentioning
confidence: 87%
“…Canan ve arkadaşları (21) 6-9 yaş arası öğrenciler üzerinde yürüttükleri çalışmada bu parazitin görülme oranını 8-9 yaş grubu öğrencilerde (%14,7), 6-7 yaş grubunda bulunan öğrencilere (%5,5) kıyasla daha yüksek bulmuşlardır. Yapılan iki çalışmanın (10,21) sonuçları, bu çalışmamızdan elde edilen sonuçlarla uyumlu bulunmuştur. Okul öncesi çocuklarda sıklığın daha düşük olması, genel temizliğin görevliler tarafından yapılması ve dış ortam ile ilişkilerinin daha az olmasından kaynaklanıyor olabilir.…”
Section: Discussionunclassified
“…Bu parazitoz kız öğrencilerin %22,9'unda; erkek öğrencilerin %29,9'unda saptandı (Tablo 1). Bağırsak parazitinin cinsiyet ayırımı gözetmeksizin her bireyde gözlenebileceğini gösteren çalışmalar (10,16,22) bulunmakla birlikte cinsiyete göre farklı sonuçlar da bildirilmiştir (18,23…”
Section: Discussionunclassified